Associations among mindfulness, self-compassion, and bullying in early adolescence - Gonynor, Kelly Ann, author; Riggs, Nathaniel, advisor; Coatsworth, Doug, committee member; Crowley, John, committee member (Colorado State University. Libraries, 2016)
Bullying is defined as a particular kind of aggression that involves power imbalance and repeated intentionally harmful behavior directed toward another person. The negative effects of bullying include school dissatisfaction, depressive symptoms, and elevated risk of suicide attempts. Due to the negative effects of bullying, researchers continue to test factors associated with bullying. The purpose of this study was to explore the relationships among mindfulness, self-compassion, bullying perpetration, and bullying victimization. It was hypothesized that mindfulness and self-compassion would be significantly negatively associated with bullying perpetration and bullying victimization in middle school youth. One hundred and eighty-two 7th and 8th grade students completed pretest and posttest surveys. Multiple linear regression analyses were conducted in SPSS to examine associations among mindfulness, self-compassion, bullying perpetration, and bullying victimization in middle school youth. Findings demonstrated that mindfulness was significantly negatively associated with bullying perpetration and victimization, such that more mindful youth were less likely to bully and be victims of bullying. Results also demonstrated that self-compassion was significantly negatively associated with bullying victimization, indicating more self-compassionate youth were less likely to be victims of bullying. These results highlight two potential protective factors against bullying perpetration and victimization. Next steps include investigating these relationships longitudinally and understanding implications for prevention and intervention work.